An evaluation of the accessibility of top-ranking university websites: Accessibility rates from 2005 to 2015 - Tahani Jaser Alahmadi; Steve Drew (Journal of Open, Flexible and Distance Learning, 2017)
Accessibility evaluation is an important equity step in assessing effectiveness and usefulness of online learning materials for disabled students. With popular uptake of blended and online learning it is timely to evaluate the accessibility attained by universities in their websites and Learning Management Systems (LMS) .The present study considers this question for the period 2005 through 2015. Previous studies in this area have indicated that university websites have become gradually inaccessible, as the complexity of their content increases, and that the amount of attention being paid to this problem by the universities is low. This study employed a comparative quantitative method, and a random sample of universities’ websites was evaluated using the accessibility evaluation tool designed by AChecker. The inclusion of the specific universities chosen for this study was based on their ranking in the world, and/or in the Oceania and Arab regions. Moreover, the evaluation is organised by page type: homepage, administration page or course description/syllabus page. Thus, through a statistical and empirical study, we demonstrated that there was no significant improvement in the accessibility of universities’ web sites between 2005 and 2015. Furthermore, access to media and document files had the most influential accessibility errors. In addition, there were 27,308 (33%) total home page errors among the 180 evaluated pages from 60 of the top world, Oceania and Arab universities’ sites. There are no significant differences in accessibility level between top-ranking universities in developed or developing countries. Therefore, with participation rate at universities expanding world-wide and equity being a common corporate theme there is a growing need for universities to commit to and responsibly address accessibility to online learning materials for disabled students.